A Severe Case of Biparietal Thinning in a Medieval Skull From a Northern Italy Necropolis. Issue 1 (January 2022) - Tonina, Enrica; Larentis, Omar; Tesi, Chiara; Fusco, Roberta; Campagnolo, Monica; Licata, Marta
Abstract : Abstract: This study aims at presenting a case of symmetrical and bilateral thinning observed in a skull belonging to the skeleton of a mature woman from the medieval cemetery of Caravate (north Italy). Macroscopical, radiological, and histological analyses were performed to investigate the condition. The analyses allowed us to detect a progressive loss of both the outer table and the diploe, and the sparing of the inner table. As a controversial condition in the clinical and paleopathological literature, this case poses some difficulties in discussing the differential diagnosis. However, the sex determination, estimation of the age-at-death and different characteristics observed at the level of the postcranial bones, in particular the fractures recorded on different vertebral bodies, allowed us to correlate the biparietal thinning found in this subject to ageing and osteoporosis.